Penerapan Metode Bercerita Dalam Optimalisasi Kemampuan Bahasa Reseptif Anak Usia 5-6 Tahun di TK Negeri 02 Tenggarong. - Fachrul Rozie; Rina Ayu Marcela (JURNAL LENTERA ANAK, 2020)
This study aims to describe the method of storytelling in optimizing receptive language skills. This study uses a qualitative research approach with a type of case study research.The results of the study show that in (1) planning the storytelling method, the teacher prepares RPPM and RPPH, the teacher adjusts the story to the theme to be discussed, determines the form or technique of storytelling, determines and prepares materials and tools to be used when telling stories according to the techniques set, and adjust the sitting position of the child before starting the story telling activity. (2) The implementation of storytelling activities is that the teacher implements a storytelling method according to the stages of storytelling, and the techniques used by the teacher when telling stories are different in each center. (3) The development of receptive language skills of children aged 5-6 years in 02 Tenggarong State Kindergarten have reached the expected criteria. The development of receptive language skills in children is developed in accordance with the indicators of its development, through activities designed so that children can reach the standard level of achievement of child development.